THE USAGE OF VIDEO IN TEACHING VOCABULARY FOR YOUNG LEARNERS - Kharisma Naidi Warnanda Sabgini; Triastama Wiraatmaja (STKIP Persada Khatulistiwa Sintang, 2023)
Teaching vocabulary to young learners is essential. Therefore, the teacher tries to be creative to attract the young learners’ attention during the learning process. One of the strategies to attract young learners’ attention is using video. Many studies seek the effectiveness of using video to teach vocabulary. However, the studies were mainly conducted quantitatively. Meanwhile, this study is a primary interpretative qualitative study that seeks the usage of video in teaching young learners and the response toward it. The researcher employed human instruments, non-participant observers, and document analysis to achieve triangulation. The data are collected until no new data is forthcoming. Then, the data is analyzed based on the available theory. Based on the data, the student-teachers used video to teach young learners vocabulary as media. The student-teachers employed the video to present, practice, and produce new words. The student-teachers employed the video by active viewing, freeze frame, and reproduction. The young learners’ response toward the usage of video is positive. This research discovered that there had been an active engagement between student-teacher and young learners as well as among your learners.